Manure Management : An Overview and Assessment of Policy Instruments in the Netherlands - Backus, Ge B. C. (Washington, DC: World Bank, 2018)
This working paper provides an overview and assessment of Dutch manure management policy instruments from 1984 to 2016. The most successful and cost effective measures have included restrictions on manure spreading, the creation of a national Manure Bank as an offtake of last resort, the requirement to inject manure into soil, support for flagship farms, and limits on farm size managed under the mineral input registration system. The various quota systems that have been implemented have proven costly for industry and the public sector alike, but have prevented livestock numbers and related pollution problems from increasing further. Ever stricter limits on the application of manure to soil, for example, have imposed costs but shown positive results. Applications of manure nitrogen decreased from 447 kg per ha in 1980 to 326 kg per ha in 2010, and applications of manure phosphate decreased from 160 kg per ha to 84 kg per ha over the same period. Dutch manure management policies have generally increased farmers’ incentives to seek valuable uses of manure. The costs of manure policy to the public sector have also been relatively high, with monitoring, enforcement, and registration averaging around 900 euro per farm per year. Part of the effectiveness of Dutch manure policy has been owed to its incrementalism. Restrictive measures have generally been designed to increase in stringency over time and allowed industry to adapt. Dutch manure policy has, however, cost the life of many of the country’s less-efficient farms. The number of pig farms in the Netherlands decreased from 34,000 in 1984 to 5,000 in 2015. Lessons learned include the effectiveness of gradually tightening standards, using combinations of sticks and carrots, and regularly evaluating policies. Promising approaches include the coupling of land and animals, and manure processing.